Evaluación de tres niveles de Buclizina, para cerdos durante la fase de crecimieto y engorde - Chimbo Tamami, Marcia Jasmin (2020)
In this investigation we evaluate three Buclizine levels as appetite stimulant for pigs during the growing and fattening stage, to determine the best level (0.025; 0.05; 0,1 mg) of Buclizine in the bristles diet at the growing and fattening stage, to compare the weight gain of three Buclizine levels in growing and fattening stages, to establish possible changes in blood parameters of animals in the study and lastly, to determine the economic and cost-benefit analysis. For this investigation, the experimental design used was a completely randomized block design (DBCA) with 4 treatments and 6 repetitions, with a total of 24 experimental units, Landrace bristles with a live weight of ± 18 kg at the beginning of the investigation. The experimental results show that there is an important statistical significance (*) as promises for the proposed treatments. Based on the results obtained, we determined that the T3 treatment (Buclizine 0.050mg / kg / animal / week) was the best level of Buclizina inclusion for both the growing and fattening stages, presenting the best values and high in weight gain, efficiency and food conversion. Making a comparison between Buclizine Hydrochloride levels implemented in the investigation, we can see that T3 treatment yields a final weight of 53.83 kg, ± 5 kg over T1 treatment which has the poorest results (48,5 Kg) to T3, and ± 6 Kg over T2 and T4 which totaled 47 Kg of final weight, for the benefit of treatment T3 (Buclizine 0.05mg / kg / animal / week) I see the best benefit ratio between the treatments at an index of $ 1.88, which tells us that for every inverted dollar within the investigation, that dollar has recovered, and a gain of 88 cents.